Measuring Return and Risk of the Investment Portfolio for Agricultural Sector Companies Analytical Research in Iraq Stock Exchange (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research aims to measure the revenue and risk of the agricultural investment portfolio of the companies of agricultural sector, which represented by group of private sector companies for the period from 2012 to 2017. This research consists of three main paragraphs. The first paragraph of the research deals with research methodology and measurement tools to be link between theoretical and practical aspects focuses on definition the scientific methodology of research to confirm the theoretical facts and hypotheses on which the research was based. The second paragraph deals with the conceptual framework of the investment portfolio and the conceptual framework of revenue and risk and the relationship between them. The third paragraph represents the practical aspect of the research, which focuses on the analysis of indicators of measurement of revenue and risk of the investment portfolio of the private agricultural sector. Analyses based on the annual data. The research concluded that there is a relationship of effect and correlation that makes the risk and revenue in linear relationship and the increasing in revenue results by risks increase.